Upaya Guru KB Insan Kamil Kartasura dalam Menjaga Kesehatan Anak Melalui Program Gizi, PHBS, dan Imunisasi: Efforts of KB Teacher Insan Kamil Kartasura in Maintaining Children's Health Through Nutrition, PHBS, and Immunization Programs - Virania Kusuma Dewi; Endah Tejaningsih (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2025)
Early childhood health is an important aspect that can affect the quality of children's growth and development. So that early childhood education programs Institutions have a strategic role in ensuring the fulfillment of nutrition, habituation of Clean and Healthy Living Behavior, and support for immunization programs. This study aims to describe the implementation of nutritional fulfillment, habituation of Clean and Healthy Living Behavior, and immunization programs to health examinations in KB Insan Kamil Kartasura. This study uses a qualitative approach through interview techniques and documentation with teachers as the main informants. The results of the study show that nutritional fulfillment is carried out through the Nutritious Eating program, the provision of healthy provisions, restrictions on snacks, and the provision of water and nutritious lunches for full-day classes. The implementation habituation of Clean and Healthy Living Behavior is carried out through the habit of washing hands, maintaining personal and environmental hygiene, and regular nail hygiene checks. Meanwhile, the immunization program and health checks are carried out through the same kerha as the health center for periodic checkups twice a year and in collaboration with the Syifa Medika clinic for monthly checkups. This study concludes that KB Insan Kamil Kartasura has carried out efforts to maintain children's health through programs carried out to improve the quality of health services in early childhood education programs.